Study of metallic nano-structures formed in liquids by large pulsed laser radiation spots using transmission electron microscopy - Samuel Sánchez-Torres; Brenda-Lizeth Pérez-García; Samuel Tehuacanero-Cuapa; Alejandro Crespo-Sosa (Nano Express)
Pulsed Laser Ablation in Liquids (PLAL) represents a prominent method for synthesising metallic nanoparticles and nano-alloys. This technique offers the potential precise control over the process and resulting products. However, a comprehensive description of the underlying mechanisms is still necessary to enhance control. Our investigation involved the utilisation of low fluence 6 ns laser pulses on 35 mm ^2 areas of thin films comprising layers of Ag , Pt , and Au to investigate the nano-structures and alloys obtained. The large laser spot produced nano-structures with peculiar morphological characteristics. Their analysis by High-Resolution Transmission Electron Microscopy (HRTEM) confirms that the early stages of the ablation plume play an essential role in the nucleation of nano-structures when the ablating metals have a strong interaction with the fluid, which has surpassed its critical temperature and pressure.